Education for Sustainable Development (ESD) and Global Citizenship for India - Atasi Mohanty; Ashraf Alam; Aashish Mohanty (Journal of Education for Sustainable Development Studies, 2024)
This research paper explores the pivotal role of education in advancing sustainable development goals (SDGs) through an in-depth analysis of various indices, initiatives, and frameworks utilized to monitor progress and catalyze action. Beginning with an overview of the SDGs as a global blueprint for achieving a more equitable, prosperous, and sustainable world by 2030, the paper digs deep into the involved interaction between education and sustainable development. Central to this research is the examination of tools such as the Social Progress Index (SPI) and the SDG India Index, which provide comprehensive assessments of societal progress vis-à-vis the SDGs, offering decision-makers and stakeholders valuable insights into areas of strength and areas requiring intervention. The paper spotlights India’s pioneering initiative, the SDG India Index, which tracks progress at the state level across 13 out of the 17 SDGs, demonstrating how countries adapt global frameworks to address national priorities and challenges. Emphasizing education’s transformative potential, this investigation explains how early childhood, primary, and secondary education serve as catalysts for social, economic, and environmental progress, fostering critical thinking skills and instilling values essential for addressing complex global challenges. Furthermore, the paper emphasizes the SDG India Index’s role as a catalyst for change, facilitating evidence-based policymaking, fostering accountability, and mobilizing stakeholders towards shared goals, highlighting the existing data gaps, particularly concerning Goals 12, 13, and 14, emphasizing the need for strengthened statistical systems to ensure accurate assessment and effective interventions.